2020
DOI: 10.2147/copd.s229505
|View full text |Cite
|
Sign up to set email alerts
|

<p>Plasma Metabolomics and Lipidomics Reveal Perturbed Metabolites in Different Disease Stages of Chronic Obstructive Pulmonary Disease</p>

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a common disease characterized by persistent respiratory symptoms and airflow restriction. It is usually manifested as airway and/or alveolar abnormalities caused by significant exposure to harmful particulates or gases. Objective: We aim to explore plasma metabolomic changes in the acute exacerbation stage of COPD (AECOPD) and stable stage of COPD (Stable COPD) to identify potential biomarkers for diagnosis or prognosis in clinical practice. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…In a study of 133 patients with COPD and 101 normal pulmonary function controls from Peking University, China, changes in the amino acid metabolism pathways that suggest a protein breakdown were reported in COPD patients [ 25 ]. Gillenwater et al reported COPD associations with glutamate; arginine and proline metabolism; lysine metabolism; methionine; cysteine; SAM and taurine metabolism; and phenylalanine metabolism [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 133 patients with COPD and 101 normal pulmonary function controls from Peking University, China, changes in the amino acid metabolism pathways that suggest a protein breakdown were reported in COPD patients [ 25 ]. Gillenwater et al reported COPD associations with glutamate; arginine and proline metabolism; lysine metabolism; methionine; cysteine; SAM and taurine metabolism; and phenylalanine metabolism [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a serum NMR study of 157 subjects from the SPIROMICS cohort, 20 out of 27 metabolites (mostly amino acids, including tryptophan, and BCAAs) were lower in those with at least one exacerbation during the preceding year [ 42 ]. In the Peking University China study, there was a subset of the matched study of 48 healthy controls, 48 stable COPD patients, and 48 patients with an acute exacerbation of COPD (AECOPD), in which glutamylphenylalanine and taurine were lower with AECOPD [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALT, alanine transaminase; AST, aspartate transaminase; INR, international normalized ratio metabolism. 36 Porphyrin and its derivative compounds are widely present in vital organelles related to energy transfer, and play a key role in blood cells carrying oxygen for respiration. 37 In the past few years, researchers have found that acetic acid, sorbitol, D-lactic acid, hexanoic acid, L-naphthalenamine, butanoic acid, phosphoric acid, D-glucitol, and glucose concentration in the serum samples of patients with HBV were the strongest segregation between cirrhosis group and non-cirrhosis group.…”
Section: Discussionmentioning
confidence: 99%
“…Khosla and Fungwe 35 provided information that increasing the intake of linoleic acid has a significant beneficial effect on the progression of atherosclerosis. Phenylalanine is one of the essential amino acids, and the activity level of the phenylalanine metabolism pathway may reflect the synthesis and breakdown state of the systematic protein, and together with tyrosine, it synthesizes important biomolecules and takes part in carbohydrate and fat metabolism 36 . Porphyrin and its derivative compounds are widely present in vital organelles related to energy transfer, and play a key role in blood cells carrying oxygen for respiration 37 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabolomics has been widely applied in various elds, such as drug toxicity, disease diagnosis, and pharmacodynamic study [40][41][42]. To elucidate the mechanisms though which AZI ameliorated CSE-induced airway epithelial barrier dysfunction, we performed metabolomics pro ling.…”
Section: Discussionmentioning
confidence: 99%